Zur and zinc increase expression of E. coli ribosomal protein L31 through RNA-mediated repression of the repressor L31p. Issue 22 (19th December 2022) - Rasmussen, Rebecca A; Wang, Suning; Camarillo, Jeannie M; Sosnowski, Victoria; Cho, Byoung-Kyu; Goo, Young Ah; Lucks, Julius B; O'Halloran, Thomas V
Abstract: Bacteria can adapt in response to numerous stress conditions. One such stress condition is zinc depletion. The zinc-sensing transcription factor Zur regulates the way numerous bacterial species respond to severe changes in zinc availability. Under zinc sufficient conditions, Zn-loaded Zur (Zn2 -Zur) is well-known to repress transcription of genes encoding zinc uptake transporters and paralogues of a few ribosomal proteins. Here, we report the discovery and mechanistic basis for the ability of Zur to up-regulate expression of the ribosomal protein L31 in response to zinc in E. coli . Through genetic mutations and reporter gene assays, we find that Zur achieves the up-regulation of L31 through a double repression cascade by which Zur first represses the transcription of L31p, a zinc-lacking paralogue of L31, which in turn represses the translation of L31. Mutational analyses show that translational repression by L31p requires an RNA hairpin structure within the l31 mRNA and involves the N-terminus of the L31p protein. This work uncovers a new genetic network that allows bacteria to respond to host-induced nutrient limiting conditions through a sophisticated ribosomal protein switching mechanism. Graphical Abstract: